The Role of Future Work Self Towards Career Search Efficacy Among Undergraduate Students - Gunawan, Gianti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
In adolescence and adulthood, individuals have the developmental task of finding the right career. Individuals can explore their career goals through their experiences, interests, talents, and skill development. This ability leads to career search efficacy. Bandung is a city with policies and access to information that is easy to reach by various parties. This makes the scope of a person to find a field of work wider. Based on these phenomena, researchers are interested in seeing the role of career search efficacy on future work self in undergraduate students in Bandung. Future work self is a promising concept for understanding how young people view and plan their careers in the contemporary workplace. The participants of this study were 101 students in Bandung city which were obtained through accidental sampling. This study utilized the Career Search Efficacy Scale and the Future Work Self measurement tool. The data analysis technique used was simple linear regression. The results showed that future work self does not significantly influence undergraduate students' career search efficacy in Bandung.